Działalność Archiwum Uniwersytetu Kardynała Stefana Wyszyńskiego w W arszawie w świetle jego sprawozdawczości w latach 2003-2015 - Poletyło, Roman (Saeculum Christianum. Pismo Historyczne, 2016)
The 15th anniversary of the establishment of the Cardinal Stefan Wyszyński University (UKSW) archive is a good moment to reflect on its operation. Its annual reports enable us to recognize the scale and quality of the archive’s operation. Reports prepared between 2003 and 2015 for various purposes and authorities show how the archive has fulfilled its basic duties. The quality of UKSW’s archive is monitored by the State Archive in Warsaw. As a interfaculty unit of UKSW, the archive also comes under the authority of one of the University’s deputy vice-chancellors. The archive mainly reports to these principal bodies on an annual basis. The archive holds the records of the Warsaw Theological Academy which was later transformed into UKSW